Translating Rāma as a Proto-Muḥammadan Prophet: Masīḥ’s Mas̱navī-i Rām va Sītā - Keshavmurthy, Prashant (Numen, 2018)
How have religious communities imagined the scriptures of other communities? In answering this question, this article aims to nuance our understanding of pre-colonial and self-consciously Islamic translations into Persian of Indic language texts understood to be Hindu by considering Masīḥ’s early 17th-century Mas̱navī-i Rām va Sītā, a Persian translation of Vālmīki’s Sanskrit epic, the Rāmāyaṇa (circa 2nd century bce). It opens by remarking on a shift in the study of the relations between poetics and politics in Persian translations of Indic texts. Then, attempting to refine our understanding of this relation, it takes issue with prior studies of this poem before answering the following questions these studies fail to pose: how does the prophetological metaphysics of the prefatory chapters relate to the poetics of emotion in the main body of the tale? And what does this relation let us infer of Masīḥ’s theological conception of translation?